Manajemen Mindfulness pada Mahasiswa - Puput Mulyono; Kresna Agung Yudhianto (Lembaga Pengembangan Kinerja Dosen, 2025)
Mindfulness or mindfulness is increasingly promoted in Western countries as a psychological strategy to improve emotional regulation and self-control, including in the context of reducing aggressive behavior, especially when individuals experience a state of exhaustion or ego depletion. However, the effectiveness of this approach in the context of non-Western cultures has not been widely explored. This study aims to replicate the study of Yusainy and Lawrence (2015) in Indonesia to test whether the induction of mindfulness can also moderate aggression after ego depletion in different cultural environments. This experimental research involved 119 Indonesian students as participants. Using a laboratory design, participants were divided into conditions of induction of mindfulness and control, and were asked to complete a reaction time competition task that had been modified to measure aggression (through the intensity of the sound explosions released against a fictitious opponent). In addition, an additional measure of the frequency of delayed maximum burst release was used to evaluate more subtle forms of aggression, particularly in female participants. The results showed that mindfulness significantly moderated the relationship between ego-depletion and aggression conditions, especially in low- to moderate-provoking situations. Mindfulness induction also showed improved self-control performance after participants completed aggression tasks. Another important finding is that the positive effect of mindfulness on aggression reduction is most visible in more subtle indicators of aggression, especially in groups of women who experience ego thinning. In conclusion, the results of this study reinforce the cross-cultural validity of the Western mindfulness approach and emphasize the importance of using more sensitive aggression measures, especially in assessing the effects of psychological interventions on female populations in non-Western cultures such as Indonesia.